Experimental Characterisation of Polyethylene Terephthalate (PET) Bottle Eco-Bricks - Taaffe, J.; O’Sullivan, S.; Rahman, Muhammad; Pakrashi, V. (Elsevier, 2014)
This paper addresses the issue of recycling waste plastic by considering the feasibility of use of Eco-bricks for constructional purposes. The Eco-bricks are formed by packing plastic within Polyethylene Terephthalate (PET) bottles. Guidelines were provided for the construction of Eco-bricks. Experiments were carried out to characterise some of the properties of these bricks. Compression test, sound insulation assessment and light transmission were considered in this regard and compared with traditional construction materials and conditions. Possible applications of Eco-bricks were discussed. The paper presents the first attempt to characterise these bricks and the results encourage future use of them to a significantly wider extent and for various purposes.